Pengembangan Bahan Ajar Pendidikan Agama Islam Berbasis Kontekstual Untuk Meningkatkan Hasil Belajar di SMP Swasta Al Washliyah 15 Medan - Shoumi, Putri Nur; Setiawan, Hasrian Rudi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to develop contextual-based Islamic Religious Education (PAI) teaching materials that can improve student learning outcomes at **SMP Swasta Al Washliyah 15 Medan**. Contextual-based teaching materials are expected to help students relate the learning material to real-life situations they experience, resulting in a deeper and more applicable understanding of religious concepts. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. This study involves students of SMP Swasta Al Washliyah 15 Medan as research subjects. The results show that contextual-based PAI teaching materials are proven to be effective in improving student learning outcomes, as evidenced by an increase in learning evaluation scores and positive responses from students toward the developed materials. This research is expected to serve as a reference for teachers in designing more relevant and contextual teaching materials to improve the quality of PAI learning.